2003
DOI: 10.1634/stemcells.21-1-50
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Cells from Wharton's Jelly Form Neurons and Glia

Abstract: We have identified an easily attainable source of primitive, potentially multipotent stem cells from Wharton's jelly, the matrix of umbilical cord. Wharton's jelly cells have been propagated in culture for more than 80 population doublings. Several markers for stem cells, including c-kit (CD117), and telomerase activity are expressed in these cells. Treatment with basic fibroblast growth factor overnight and low-serum media plus butylated hydroxyanisole and dimethylsulfoxide induced Wharton's jelly cells to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
439
1
9

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 563 publications
(473 citation statements)
references
References 39 publications
24
439
1
9
Order By: Relevance
“…It was also described that MSCs do not require oxidative phosphor-ylation to survive ( Dos Funes et al, 2007) instead, hypoxia prolongs the lifespan of these cells, increases their proliferative capacity and reduces differentiation ( Fehrer et al, 2007). Several studies in recent years investigated the biological activity of HMSCs and their in vitro differentiation in neuroglial-like cells Mitchell et al, 2003). In this study, HMSCs were in vitro differentiated with neurogenic med-ium.…”
Section: Groupmentioning
confidence: 95%
See 2 more Smart Citations
“…It was also described that MSCs do not require oxidative phosphor-ylation to survive ( Dos Funes et al, 2007) instead, hypoxia prolongs the lifespan of these cells, increases their proliferative capacity and reduces differentiation ( Fehrer et al, 2007). Several studies in recent years investigated the biological activity of HMSCs and their in vitro differentiation in neuroglial-like cells Mitchell et al, 2003). In this study, HMSCs were in vitro differentiated with neurogenic med-ium.…”
Section: Groupmentioning
confidence: 95%
“…After 96 h the regular mesenchymal-like shape of the cells changed and the cells became exceedingly long. Morphologically it was observed the formation of neuroglial-like cells after differentiation which were positively stained for the typical specific neuronal markers ( Choong et al, 2007;Fu et al, 2004;Mitchell et al, 2003) such as the GFAP, the GAP-43 and the NeuN attesting a clear successful differentiation. The morphologic and biochemical characteristics of neuroglial-like cells are already described but the mechanism by which stem cells differentiate into neuroglial-like cells is still unknown.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Umbilical cord blood is a source of both pluripotent stem cells (Kogler et al, 2004) and haematopoietic stem cells. The umbilical cord matrix was found to be a source of multipotent stem cells (Mitchell et al, 2003, Wang et al, 2004. When transplanted to an allo-recipient, these cells show low immunogenicity and can even have localized immunosuppressive functions.…”
Section: Umbilical Cord-derived Stem Cellsmentioning
confidence: 99%
“…Previous studies have reported the in vitro differentiation of hUCMSCs into mesoderm-type cells, such as osteoblasts, chondrocytes, adipocytes, cardiomyocytes, skeletal muscle cells, and endothelial cells Conconi et al 2006;Hoerstrup et al 2002;Sarugaser et al 2005;Schmidt et al 2006;Wang et al 2004;Wu et al 2007) as well as cells of nonmesoderm lineages, including neurocytes (Wang et al 2004;Fu et al 2004;Ma et al 2005;Mitchell et al 2003). hUC blood-derived MSCs enhanced wound healing in mice by differentiating into keratinocytes (Luo et al 2010).…”
Section: Introductionmentioning
confidence: 99%